1985
DOI: 10.1017/s0022029900024316
|View full text |Cite
|
Sign up to set email alerts
|

Epimerization of lactose to free lactulose in heated model milk solutions

Abstract: The kinetics of the epimerization of lactose to lactulose were determined for two ' model milk' solutions, one containing lactose and the other lactose and lysine. The lysine was added to lactose to determine whether amino groups of proteins act as base catalysts promoting the production of free lactulose. The presence of lysine actually reduced the rate of production of free lactulose, presumably by the formation of amino-sugar complexes. The rate of production of free lactulose over the range of processing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

1986
1986
1997
1997

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
0
4
1
Order By: Relevance
“…The lactulose content of the ultrafiltrate was found to be much lower than that of milk diluted with ultrafiltrate, suggesting that the milk protein may have had a catalytic effect on its formation. This is in contrast to the results of Greig & Payne (1985), who found that lactulose was formed more rapidly in ultrafiltrate than in milk. However, increasing the protein content of the milk reduced the amount of lactulose recovered so that the sample containing 1-68 % total N contained approximately the same amount of lactulose as the ultrafiltrate.…”
Section: Effect Of Protein Concentrationcontrasting
confidence: 99%
“…The lactulose content of the ultrafiltrate was found to be much lower than that of milk diluted with ultrafiltrate, suggesting that the milk protein may have had a catalytic effect on its formation. This is in contrast to the results of Greig & Payne (1985), who found that lactulose was formed more rapidly in ultrafiltrate than in milk. However, increasing the protein content of the milk reduced the amount of lactulose recovered so that the sample containing 1-68 % total N contained approximately the same amount of lactulose as the ultrafiltrate.…”
Section: Effect Of Protein Concentrationcontrasting
confidence: 99%
“…They removed the sugars from processed milk by dialysis and then converted them to their trimethylsilyl (TMS) derivatives with TMS imidazole, which were then separated and quantified by HPLC. Greig & Payne (1985) also determined lactulose by HPLC, but without a derivatizing step. They detected less lactulose in a UHT milk than was measured in a sample of the same milk by the enzymic method of Andrews (1984).…”
Section: Chromatographic Methodsmentioning
confidence: 99%
“…Andrews (19856) also showed that the UHT presterilization and in-bottle processes for sterilized milk were additive with respect to their production of lactulose in the milk. Greig & Payne (1985) found that when a 4 % (w/v) lactose solution was heated for up to a few hours at 125 °C, the lactulose concentration reached a maximum of 1200 mg/100 ml. They also showed that when a lactulose solution was heated, some was isomerized to lactose.…”
Section: Factors Affecting the Lactulose Content Of Uht And Sterilizementioning
confidence: 99%
“…The kinetics of epimerization of lactose to lactulose were studied in model milk solutions (Greig and Payne, 1985). Two milk solutions were studied -one containing lactose and the other containing lactose and lysine.…”
Section: Lactose: Chemical Derivativesmentioning
confidence: 99%
“…There is evidence from studies on milk ultrafiltrates that protein may inhibit the formation of lactulose (Greig and Payne, 1985). Similarly, the presence of amino groups in the form of N-acetyl-L-lysine led to a decrease in lactulose formation (Olano et al, 1989).…”
Section: Reaction Chemistry Of Lactosementioning
confidence: 99%